Double gate lateral IGBT on partial membrane - 罗小蓉 雷磊 张伟 张波 李肇基 (Journal of semiconductors, 2010)
A new SOILIGBT（lateral insulated-gate bipolar transistor） with cathode-and anode-gates on partial membrane is proposed.A low on-state resistance is achieved when a negative voltage is applied to the anode gate.In the blocking state,the cathode gate is shortened to the cathode and the anode gate is shortened to the anode,leading to a fast switching speed.Moreover,the removal of the partial silicon substrate under the drift region avoids collecting charges beneath the buried oxide,which releases potential lines below the membrane,yielding an enhanced breakdown voltage（BV）.Furthermore,a high switching speed is obtained due to the absence of the drain-substrate capacitance. Lastly,a combination of uniformity and variation in lateral doping profiles helps to achieve a high BV and low special on-resistance.Compared with a conventional LIGBT,the proposed structure exhibits high current capability,low special on-resistance,and double the BV.